Impact of extracorporeal cardiopulmonary resuscitation on outcomes of elderly patients who had out-of-hospital cardiac arrests: a single-centre retrospective analysis. Issue 5 (18th May 2018) - Goto, Tadahiro; Morita, Sachiko; Kitamura, Tetsuhisa; Natsukawa, Tomoaki; Sawano, Hirotaka; Hayashi, Yasuyuki; Kai, Tatsuro
Abstract : Objectives: Little is known about the effectiveness of extracorporeal cardiopulmonary resuscitation (ECPR) for elderly patients who had out-of-hospital cardiac arrest (OHCA). The aim of this study was to examine the impact of age on outcomes among patients who had OHCA treated with ECPR. Design: Single-centre retrospective cohort study. Setting: A critical care centre that covers a population of approximately 1 million residents. Participants: Patients who had consecutive OHCA aged ≥18 years who underwent ECPR from 2005 to 2013. Primary and secondary outcome measures: Primary outcomes were 1 month neurologically favourable outcomes and survival. To determine the association between advanced age and each outcome, we fitted multivariable logistic regression models using: (1) age as a continuous variable and (2) age as a categorical variable (<50 years, 50–59 years, 60–69 years and ≥70 years). Results: Overall, 144 patients who had OHCA who underwent ECPR were eligible for our analyses. The proportion of neurologically favourable outcomes was 7%, while survival was 19% in patients who had OHCA. After the adjustment for potential confounders, while advanced age was non-significantly associated with neurologically favourable outcomes (adjusted OR 0.96 (95% CI 0.91 to 1.01), p=0.08), the association between advanced age and the poor survival rate was significant (adjusted OR 0.96 (95% CI 0.93 to 0.99), p=0.04). Additionally, compared with age <50 years, age ≥70 years was non-significantly associated with poor neurological outcomes (adjusted OR 0.08 (95% CI 0.01 to 1.00), p=0.051), whereas age ≥70 years was significantly associated with worse survival in the adjusted model (adjusted OR 0.14 (95% CI 0.03 to 0.80), p=0.03). Conclusions: In our analysis of consecutive OHCA data from a critical care hospital in an urban area of Japan, we found that advanced age was associated with the lower rate of 1-month survival in patients who had OHCA who underwent ECPR. Although larger studies are required to confirm these results, our findings suggest that ECPR may not be beneficial for patients who had OHCA aged ≥70 years.